2011
DOI: 10.1080/15257770.2011.562475
|View full text |Cite
|
Sign up to set email alerts
|

An Rna Aptamer Containing Two Binding Sites Against the HCV Minus-Ires Domain I

Abstract: The higher order structure of HCV (-)IRES containing five stem-loop structures (domain I) is essential for HCV replication because the viral RNA-dependent RNA polymerase, NS5B, recognizes it as the initiation site for plus-strand synthesis. To inhibit a de novo synthesis of plus-strand RNA molecules, in vitro selection against (-)IRES domain I was performed. One of the obtained aptamers, AP30, contained two consensus sequences within a random sequence region. Two consensus sequences form two apical loops and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Its consensus sequences 5'-UGGAUC-3' and 5'-GAGUAC-3', which were complementary to the SL-E1 and SL-D1 loops in the domain I were responsible for this effect. In this way they prevented attachment of viral RNA polymerase, NS5B, mentioned above [ 92 , 105 ]. Kikuchi et al obtained RNA aptamer containing loop structure with a consensus sequence 5'-UAUGGCU-3', complementary to the loop of the IRES domain II.…”
Section: Aptamers In the Treatment Of Viral Infectionsmentioning
confidence: 99%
“…Its consensus sequences 5'-UGGAUC-3' and 5'-GAGUAC-3', which were complementary to the SL-E1 and SL-D1 loops in the domain I were responsible for this effect. In this way they prevented attachment of viral RNA polymerase, NS5B, mentioned above [ 92 , 105 ]. Kikuchi et al obtained RNA aptamer containing loop structure with a consensus sequence 5'-UAUGGCU-3', complementary to the loop of the IRES domain II.…”
Section: Aptamers In the Treatment Of Viral Infectionsmentioning
confidence: 99%
“…Therefore, recruitment of ribosomal particles mediated by the IRES element was inhibited by the chimera HH363-24 that prevented both translation and replication in a hepatic cell line [95]. Moreover, to avoid HCV genome replication, Konno et al isolated RNA aptamers against the 3′ end of the negative strand of the virus genome [96,97]. Interestingly, a RNA aptamer, named AP30, was able to recognize this minus-IRES region and reduce positive-strand genomic RNA synthesis [96].…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…Moreover, to avoid HCV genome replication, Konno et al isolated RNA aptamers against the 3′ end of the negative strand of the virus genome [96,97]. Interestingly, a RNA aptamer, named AP30, was able to recognize this minus-IRES region and reduce positive-strand genomic RNA synthesis [96]. To inhibit HCV replication, Marton et al selected RNA aptamers against CRE element that were able to repress replication of HCV replicon in hepatic cells [98].…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…Konno et al isolated RNA aptamers specific for HCV (−) IRES domain I. They showed that this aptamer inhibited up to 50% of the NS5B-mediated positive-strand RNA synthesis [40][41][42].…”
Section: Therapeutic Aptamers For Targeting the Hcv Viral Genomementioning
confidence: 99%